(untitled) (Journal of Universal Science Research, 2024)
The article examines the method of calculating the distance to objects in the collaborative robots workspace using computer vision technologies. The results of experiments are analyzed, which reveal the dependence of measurement accuracy on various factors, such as the distance to the object and the speed of its movement. The results indicate the need to improve data processing algorithms to ensure reliable operation of robotic systems in dynamic environments. This is important for improving the efficiency of robots’ interaction with the environment.